Effects of glaciological and hydro-meteorological conditions on the glacial danger in Zailiyskiy Alatau - A. R. Medeu; T. G. Tokmagambetov; A. L. Kokarev; L. A. Yeriskovskaya; T. L. Kirenskaya; P. A. Plekhanov; N. S. Plekhanov (Лëд и снег, 2017)
A need to estimate a hazard of a mudflow stream appearance in the glacial-nival zone of the Northern slope of Zailiyskiy Alatau (Kasakhstan) is now one of the really urgent problems. The objective of this study was to inves‑ tigate influence of glacial and hydrometeorological factors on the condition of snow-glacial zone of Zailiyskiy Alatau and find out a mudflow-forming role of the mudflow centers arising due to climate warming and degra‑ dation of glaciation: periglacial lakes, intramoraine channels and reservoirs, and also talik massifs of morainic deposits. We analyzed glacial processes in the Zailiysky Alatau over a long period using meteorological data of the Almaty weather station and its close correlations with data from weather stations in the mountains. The area of glaciations was found out to be reduced after the maximum of the Little Ice Age. A combined diagram of occurrence of the mudflow manifestations and factors causing them had been constructed on the basis of sta‑ tistical data on the landslide phenomena. Glacial mudflows were the most frequent in 1960–1990, and later on activity of them became weaker. We believe, that in the next 10–20 years, the glacial mudflow hazard in Zailiys‑ kiy Alatau can sharply decrease, but at the same time, a probability of occurrence of the rainfall mudflows can increase in the mountainous zone of the ridge due the increase of areas with melted moraine and slope deposits.